Freedom of Religion and Belief in Turkey: Religion, Society and Politics - Çınar, Özgür Heval (Springer International Publishing AG, 2021)
Intro -- Contents -- About the Author -- Chapter 1: Introduction -- Chapter 2: The Religion Box on the National Identity Card: Being Compelled to Reveal One's Religion and Beliefs -- 2.1 Introduction -- 2.2 International Law Standards -- 2.2.1 European Court of Human Rights' Case Law -- 2.3 Turkey's Obligations -- 2.3.1 Turkish Law -- 2.3.2 Steps Taken After the Sinan Işık v. Turkey Judgment -- 2.4 Conclusion -- Chapter 3: The Military-Nation and Conscientious Objectors -- 3.1 Introduction -- 3.2 International Law Standards -- 3.3 Turkey's Obligations -- 3.3.1 Turkish Law -- 3.3.2 Political, Economic, Social and Cultural Aspects of Militarism -- 3.3.3 Homosexual Conscientious Objectors and the Unfit Report -- 3.4 Conclusion -- Chapter 4: Unresolved Issue: Compulsory Religious Education -- 4.1 Introduction -- 4.2 International Law Standards -- 4.2.1 European Court of Human Rights' Case Law -- 4.3 Turkey's Obligations -- 4.3.1 The History of Religious Education in Turkey -- 4.3.2 Turkish Law -- 4.4 Conclusion -- Chapter 5: Recognition of Faith Groups and the Opening of Places of Worship -- 5.1 Introduction -- 5.2 International Law Standards -- 5.2.1 European Court of Human Rights' Case Law -- 5.2.2 The EU and the Venice Commission -- 5.3 Turkey's Obligations -- 5.3.1 Turkish Law -- 5.3.1.1 Planning Regulations -- 5.3.1.2 Legal Personality -- 5.3.1.3 The Appointment of Religious Leaders -- 5.3.1.4 Teaching -- 5.4 Conclusion -- Chapter 6: The Manifestation of Religious Belief in the Public Sphere: Religious Symbols and Dress -- 6.1 Introduction -- 6.2 International Law Standards -- 6.2.1 The European Court of Human Rights' Case Law -- 6.3 Turkey's Obligations -- 6.4 Conclusion -- Index.